Anti-inflammatory study of leaf extracts of Annona Reticulata linn and HPTLC analysis (Funded Work) - KALYANI PATHAK; APAROOP DAS (International Journal of Pharma and Bio Sciences, 2019)
Anti-inflammatory activity of five different extracts of leaves of AnnonareticulataLinn. ie. Petroleum ether, Ethyl acetate, Acetone, Methanol and Water extracts were carried out by Carrageenan induced rat paw edema method. Phytochemical screening and acute toxicity study wasperformed for all the five extracts.There were significant dose-dependent anti-inflammatory activity of all five extracts.Methanolic extract was found to be shown better inhibition among the five leaf extract with reference to standard drug Aceclofenac (10 mg/kg).Orally administered doses of 500mg/kg of methanolic extract and water extract of leaves of Annonareticulataproduced 44.02% and 41.84% inhibition respectively after 3 hours. Acetone extract was also found to be significant and produced 40.21% inhibition. Petroleum ether and Ethyl acetate extracts were less significant as compared to other three extracts and standard drug aceclofenac. HPTLC fingerprint profile of themethanolic extract of Annonareticulata Linn. was also performed for detection of standard marker compound - Quercetin by the automatic TLC applicator and using the solvent system Toluene: Ethyl acetate : Formic acid in the ratio 9.0:10.0:1.6. HPTLC fingerprint of methanol extract revealed the presence of bioactive marker compound like Quercetin . Quantitative estimation of Quercetin is also carried out for standardization purpose.